2016
DOI: 10.7567/jjap.55.05fd08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sputtering pressure on crystalline quality and residual stress of AlN films deposited at 823 K on nitrided sapphire substrates by pulsed DC reactive sputtering

Abstract: Aluminum nitride (AlN) is a promising material for use in applications such as deep-ultraviolet light-emitting diodes (UV-LEDs) and surface acoustic wave (SAW) devices. In the present study, the effect of sputtering pressure on the surface morphology, crystalline quality, and residual stress of AlN films deposited at 823 K on nitrided a-plane sapphire substrates, which have high-crystalline-quality c-plane AlN thin layers, by pulsed DC reactive sputtering was investigated. The c-axis-oriented AlN films were ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…It was also reported that when the sputtering pressure increased, the collision between sputtering particles and Ar ions led to the formation of AlN (100) films [ 64 ]. Both observations have been reported by many researchers in Table 2 such as in references [ 17 , 22 , 28 , 35 , 39 , 41 , 45 ].…”
Section: Compilation Of Recipes and The Roles Of The Sputtering Pasupporting
confidence: 72%
See 1 more Smart Citation
“…It was also reported that when the sputtering pressure increased, the collision between sputtering particles and Ar ions led to the formation of AlN (100) films [ 64 ]. Both observations have been reported by many researchers in Table 2 such as in references [ 17 , 22 , 28 , 35 , 39 , 41 , 45 ].…”
Section: Compilation Of Recipes and The Roles Of The Sputtering Pasupporting
confidence: 72%
“…For each parameter, selected works that investigate its effect will be mentioned. In addition to using the works that were already summarized in Table 2 , i.e., references [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], we also highlight additional articles that are not included in that table i.e., references [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Compilation Of Recipes and The Roles Of The Sputtering Pamentioning
confidence: 99%
“…Thus, facilitating the growth of highly c-axis AlN thin-film. The target to substrate distance at 120 mm considered far enough and not favourable to the growth of c-axis AlN thin-film as most reports work on much smaller distance target to the substrate (Yang et al , 2014; Stan et al , 2015; Zhang et al , 2015; Ohtsuka, Takeuchi and Fukuyama, 2016). As the mean free path is longer, the collision between sputter particles has lower energy and not favourable for c-axis growth.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 We have investigated the effect of sputtering pressure on the crystalline quality and residual stress of AlN films deposited on the nitrided a-plane sapphire substrates at 823 K in an Ar-50 vol%N 2 gas mixture using 800 W pulsed DC sputtering. 11 We show that the optimized sputtering condition was achieved at total pressures (P total ) of 0.4-0.6 Pa. However, the polarity of AlN sputtered films was still nitrogen (c)-polar, which follows the polarity of the nitrided layer of the sapphire.…”
Section: Introductionmentioning
confidence: 88%